The impact of a simplified documentation method for the Edmonton classification system for cancer pain (ECS-CP) on clinician utilization - Tanco, Kimberson; Arthur, Joseph; Haider, Ali; Stephen, Saneese; Yennu, Sriram; Liu, Diane; Bruera, Eduardo (Supportive care in cancer, 2017)
Purpose The use of standardized pain classification systems such as the ECS-CP can assist in the assessment and management of cancer pain. However, its completion has been limited due to its perceived complexity of decoding each feature. The objectives of this study were to determine the rate of clinician documentation and completion of the ECS-CP features after revision and simplification of the response for each feature. Methods Electronic records of consecutive patient visits at the outpatient supportive care center seen by 12 palliative medicine specialists were collected at 6 months before (pre-interventional period), 6 and 24 months after (post-interventional period) the implementation of the simplified ECS-CP tool. Rate of ECS-CP documentation, completion, and analysis of patient and physician predictors were completed. Results One thousand and twelve patients’ documentation was analyzed: 343 patients, before; 341 patients, 6 months after, and 328 patients, 24 months after the intervention. ≥2/5 items were completed before the intervention, 6 months after the intervention and 24 months after intervention in 0/343 (0 %), 136/341 (40 %), and 238/328 (73 %), respectively ( p < 0.001). 5/5 items were completed before the intervention, 6 months after the intervention and 24 months after intervention in 0/343 (0 %), 131/341 (38 %), and 222/328 (68 %), respectively, ( p < 0.001). There were no patient or physician predictors found significant for successful documentation of ECS-CP. Conclusion Our findings suggest that significant simplification and intensive education is necessary for successful adoption of a scoring system. More research is needed in order to identify how to adopt tools for daily clinical practice in palliative care.